INTERNAL FACTOR OF SYSTEMAMTIC RISK MODEL WITH INFORMATION TECHNOLOGY AS INTERVENING VARIABLES TO INCREASING QUALITY OF GOVERNMENT FINANCIAL REPORTS IN INDONESIA: ACTUAL CASE FROM RIAU ISLAND PROVINCE - Am. Riyadi; Muammar Khaddafi; Fuadi F; Falahuddin F; Rico Nur Ilham (RADJA PUBLIKA, 2021)
For the realization of the vision and mission of the Riau Islands Provincial Government, improving the competence of human resources in employees is an important aspect. Human Resources is the most important asset in the company. However, in practice it is not easy for organizations to make HR as a useful asset. Organizations need to implement a competency-based HR system to eliminate conflicts between organizations and employees, because in modern management philosophy, employees are human beings who have needs, expectations that need to be heard along with potential and competencies that can be developed to achieve organizational performance and performance. The purpose of this study was to determine the direct and indirect effect of the variable competence of human resources, job relevant information and financial planning on the quality of financial reports as well as through information technology. This study uses primary data derived from questionnaires and secondary data obtained from books and related literature. The data analysis technique uses the SEM version 3.0 tool. As for the results of this study, there is a direct influence of the Financial Planning variable on the Information Technology variable having a positive path coefficient. The direct influence of the Financial Planning variable on the Financial Statement Quality variable has a positive path coefficient. The direct influence of the Information Technology variable on the Financial Statement Quality variable has a path coefficient of positive. The direct influence of the Human Resources Competency variable on the Information Technology variable has a positive path coefficient. The direct influence of the Human Resources Competency variable on the Financial Statement Quality variable has a positive path coefficient. Variable direct effect Job Relevant Information on Information Technology variables has a path coefficient of positive. The direct influence of the Job Relevant Information variable on the Financial Statement Quality variable has a positive path coefficient.